Pengaruh Kompensasi, Motivasi Kerja dan Kepuasan Kerja Sebagai Variabel Intervening Terhadap Kinerja - Garaika Garaika (JURNAL ILMIAH MANAJEMEN & BISNIS, 2020)
This study aims to examine whether the influence of compensation, work motivation, and job satisfaction as an intervening variable on the performance of lecturers and education staff of the Trisna State College of Economics. This study uses descriptive and causal research types (causality) in explaining the influence between compensation variables, work motivation, job satisfaction, and performance. In the inferential analysis phase, data analysis is assisted by a statistical program using analysis with the Structural Equation Modeling (SEM) program, which is the Smart-PLS computer analysis program. The population of this study is the lecturers and education staff of the Trisna Negara College of Economics. The sample was determined based on the purpose sampling method, with a total sample of 100 teachers and employees—data collection techniques using the method of distributing questionnaires. Compensation has a significant positive effect on job satisfaction, work motivation has a positive and significant effect on job satisfaction, compensation has a positive and significant effect on performance, work motivation has a positive and significant effect on performance and job satisfaction has a positive and significant effect on the performance of lecturers and Higher Education staff Sekolah Tinggi Ilmu Ekonomi Trsina Negara.